Small scale production of auto-battery in Nigeria:an engineering economic model. (2009)
"This work is aimed at determining the feasibility of manufacturing automobile batteries on a small scale Level. It involves an economic evaluation directed at the typical 12V, 60Ah car battery. A process analysis was done with a view to determining the scalability of the processes. A review of relevant literature gives insights on the product structure and workings, material interactions, process requirements and the various manufacturing strategies and their respective benefits The process is designed with a bias for outsourcing, a growing trend in the direction of specialization and agile product development. Thus, the process is designed for assembly as a parallel/flow line hybrid work system. Next, economic models are developed to assess costs, profit, revenue and optimal production volume. Also, breakeven and Payback Period models are developed for determining the viability of the venture.It was found that with 11 workers, the facility yields up to 1173 units of car battery per month. This requires an initial capital investment of N1, 132,160. At an initial price of N 5,500, the product is expected to generate monthly revenue of N6,450,830 at full running capacity. Thus, a profit margin of N 3,015,340 was obtained, amounting to 46.7% of total revenue. Breakeven occurs at a demand of 121 units, which is 10.3% of the monthly production capacity. This study shows the potentials and entrepreneurial opportunities of investing in the small scale manufacture of engineering products. "